2010
DOI: 10.1007/s10834-010-9182-7
|View full text |Cite
|
Sign up to set email alerts
|

Credit Card Ownership Among American High School Seniors: 1997–2008

Abstract: Credit cards, Debt, Financial literacy, High school, Jump$tart Coalition,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…In contrast, Robb and Sharpe (2009) examined credit card among students and found that students with a higher level of financial knowledge also carried significant credit card debt. More importantly, a study among US high school seniors revealed that students who hold credit cards appeared to be less financially literate than students without credit cards (Scott, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Robb and Sharpe (2009) examined credit card among students and found that students with a higher level of financial knowledge also carried significant credit card debt. More importantly, a study among US high school seniors revealed that students who hold credit cards appeared to be less financially literate than students without credit cards (Scott, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, individuals' understanding of financial markets and instruments should directly impact subsequent market behaviors and decisions. In general, the literature has borne this out, noting strong associations between knowledge and effective money management (Babiarz & Robb, 2013;Collins, 2007;Haynes-Bordas, Kiss, & Yilmazer, 2008;Hilgert, Hogarth, & Beverly, 2003;Lusardi & Mitchell, 2011;Robb, 2011;Robb & Woodyard, 2011;Scott, 2010). In many of these studies, greater levels of financial knowledge were associated with more positive financial behaviors, such as having emergency 1 † Kansas State University cliffrobb@ksu.edu 2 University of Georgia savings, credit card use, and retirement preparedness.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…For college students, it is probably their first time to manage money independently as many college students begin working for a wage and start using credit cards issued in their own names. Some borrow a sizable amount of money for the first time (Peng et al, 2007;Lyons, 2008;Xiao et al, 2009;Scott, 2010). Given their inexperience, they are usually unprepared to effectively manage money associated with high debt (Rao and Barber, 2005;Borden et al, 2008).…”
Section: Introductionmentioning
confidence: 99%